Lethal and sub‐lethal effects of faecal deltamethrin residues on dung‐feeding insects. Issue 2 (16th January 2015) - MANN, C. M.; BARNES, S.; OFFER, B.; WALL, R.
Abstract Endectocides administered to livestock to facilitate pest and parasite control may be excreted in the faeces at concentrations that are toxic to coprophagous insects, including species of ecological importance. Although much research has focused on the effects of macrocyclic lactones, relatively less attention has been given to any similar impacts of the widely used pyrethroid insecticides. Here, the effects of faecal residues of the pyrethroid deltamethrin after application to Holstein–Friesian cattle in a proprietary pour‐on formulation are examined. Freshly dropped dung was collected 1, 3, 5 and 7 days after treatment and from an untreated control group. In laboratory bioasssays, female Lucilia sericata (Diptera: Calliphoridae) blow flies matured significantly smaller egg batches and had a lower percentage of eggs hatch after feeding on dung collected for up to 5 days after treatment, compared with flies feeding on dung from untreated cattle. In the field, artificial dung pats were constructed from the collected dung and left on pastureland for 7 days before being retrieved and searched for insects. Significantly more adult Diptera emerged from the faeces of untreated cattle than from the dung of treated cattle collected on days 1 and 3 after treatment. Adult Coleoptera were found in lower numbers in the dung of treated animals compared with control dung, suggesting a repellent effect. The results indicate that deltamethrin residues in cattle faeces have a range of lethal and sub‐lethal effects on dung‐feeding insects for up to a week after treatment, but that the precise duration and nature of toxicity varies depending on the sensitivity of the insect in question.